2018
DOI: 10.1016/j.jpeds.2018.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Echocardiographic Markers of Pulmonary Vascular Disease in Asymptomatic Infants Born Preterm at One Year of Age

Abstract: In comparison with infants born at term, infants born preterm exhibit abnormal PAAT at 1-year corrected age irrespective of neonatal lung disease status, suggesting the existence of PVD beyond infancy. PAAT measurements offer a reliable, noninvasive tool for screening and longitudinal monitoring of pulmonary hemodynamics in infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
77
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(88 citation statements)
references
References 45 publications
4
77
7
Order By: Relevance
“…Levy et al showed that the presence of a PDA in preterm infants at 36 weeks PMA did not affect PAAT values measured later, at 1 year of age. However, only 4% of the patients had PDAs at 1 year of age, at the time that the PAAT values were measured . In our study, 77% of patients had PDAs at the time of PAAT measurement, and the majority had left‐to‐right shunting lesions.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Levy et al showed that the presence of a PDA in preterm infants at 36 weeks PMA did not affect PAAT values measured later, at 1 year of age. However, only 4% of the patients had PDAs at 1 year of age, at the time that the PAAT values were measured . In our study, 77% of patients had PDAs at the time of PAAT measurement, and the majority had left‐to‐right shunting lesions.…”
Section: Discussioncontrasting
confidence: 99%
“…However, our results show that PAAT, corrected for HR, does correlate with mPAP and sPAP. We also showed that our PAAT/RVET ratios in preterm infants were significantly higher than those previously published by Levy et al . Our hypothesis is that the ratio of PAAT/RVET does not correlate with PA pressures because our patients have higher heart rates and therefore shorter RVETs compared to those in previous reports .…”
Section: Discussioncontrasting
confidence: 57%
See 3 more Smart Citations